Spectral analysis of doubly $J$-nonexpanding operators - Kuzhel', S. A. (Ukrains’kyi Matematychnyi Zhurnal, 1993)
For a contracting operator in a space with an indefinite metric (i.e., for a doublyJ-nonexpanding operator) a characteristic operator-function is defined. On the basis of a detailed investigation of the properties of regular dilatations and characteristic functions of doubly $J$-nonexpanding operators, a spectral analysis of these operators is carried out.